2012
DOI: 10.1016/j.jhep.2012.05.011
|View full text |Cite
|
Sign up to set email alerts
|

A hedgehog survival pathway in ‘undead’ lipotoxic hepatocytes

Abstract: Background & Aims Ballooned hepatocytes in nonalcoholic steatohepatitis (NASH) generate sonic hedgehog (SHH). This observation is consistent with a cellular phenotype in which the cell death program has been initiated but cannot be executed. Our aim was to determine if ballooned hepatocytes have potentially disabled the cell death execution machinery, and if so, can their functional biology be modeled in vitro. Methods Immunohistochemistry was performed on human NASH specimens. In vitro studies were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 38 publications
0
63
0
Order By: Relevance
“…Short of causing cell death, lipid overload leads to ballooned hepatocytes (29), which do not progress to cell death (30). We will also discuss ways in which these metabolically stressed cells induce distinct signaling pathways, such as sonic hedgehog (30,31) and release of proinflammatory EVs (27,32,33), that contribute to lipotoxic damage.…”
Section: Free Fatty Acid-induced Proapoptotic Signaling By Death Recementioning
confidence: 99%
See 1 more Smart Citation
“…Short of causing cell death, lipid overload leads to ballooned hepatocytes (29), which do not progress to cell death (30). We will also discuss ways in which these metabolically stressed cells induce distinct signaling pathways, such as sonic hedgehog (30,31) and release of proinflammatory EVs (27,32,33), that contribute to lipotoxic damage.…”
Section: Free Fatty Acid-induced Proapoptotic Signaling By Death Recementioning
confidence: 99%
“…These cells exist in "undead" state and secrete various factors, including sonic hedgehog, to promote tissue remodeling. On this basis, Kakisaka et al (30) suggested that ballooned hepatocytes have a cellular phenotype similar to undead cells and modeled undead ballooned hepatocytes in vitro by treating caspase 9-deficient liver-derived cell lines with palmitate. Caspase 9-deficient cells were not only protected against palmitate-and LPCinduced lipoapoptosis, but also displayed increased expression of sonic hedgehog upon palmitate and LPC treatment in a JNK-dependent manner.…”
Section: Free Fatty Acid-induced Tlr and Nf-b Activationmentioning
confidence: 99%
“…Moreover, caspase 9 deprived cells are more resistant to the lipotoxic effect of fatty acids. These results may suggest how in nonalcoholic steatohepatitis, a condition that might predispose to HCC, ballooned hepatocytes that express lower level of caspase 9 compared to neighboring normal cells may escape cell death [140].…”
Section: Crosstalk Between Hh-gli Signaling and Jnkmentioning
confidence: 97%
“…Indeed, apoptosis is believed to be crucial in the pathogenesis of NASH-related cirrhosis. Special attention has been given to effector caspase-3 and caspase-7,12 and more recently, to initiator caspase-8 and caspase-9 13 14. A prevailing concept is that injured hepatocytes behave as undead cells, initiating the apoptotic process but failing to complete it, thereby providing a sustained source of apoptosis-associated molecular signals, including hedgehog, that drive liver inflammation and fibrosis 14–16…”
Section: Introductionmentioning
confidence: 99%